Etiological Profile and Clinical Outcomes Of Acute Neurotoxicity During Pediatric ALL Treatment in a Developing Country - Hashmani, Sundus; Mohsin Feroze, Anushe; Rafique, Zohra; Hamid, Syed Ahmer; Raza, Muhammad Rafie; Ashraf, Muhammad Shamvil (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the causes, clinical manifestations, and consequences of acute neurotoxicity in pediatric patients undergoing therapy for acute lymphoblastic leukemia (ALL). Study Design: A prospective longitudinal study. Place and Duration of Study: Pediatric Oncology Department, Indus Hospital and Health Network, Karachi, Pakistan, from May to Oct 2021. Methodology: Patients presenting within 48 hours of developing neurological changes were labeled to have acute neurotoxicity. Cerebrospinal fluid (CSF) analysis, neuroimaging, metabolic profile, and an electroencephalogram (EEG) were performed as needed. Neurotoxicity types, causes, and outcomes were analyzed. Results: Among the 511 children studied, 36 (7.0%) developed neurotoxicity, while the remaining 475 showed no signs of neurotoxicity at six months of follow-up and were censored from the analysis. Methotrexate leukoencephalopathy (MLE) was the most common type of neurotoxicity, affecting 16 children during intensive and maintenance treatment. Meningoencephalitis and posterior reversible encephalopathy syndrome (PRES) were identified in seven and four children, respectively. Of the 36 children with neurotoxicity, 29 (80.5%) achieved full recovery. However, seven children (19.5%) died; one due to disease recurrence and six from various complications. Conclusion: Most patients with neurotoxicity had complete recovery. The major causes of morbidity and mortality were MTX toxicity and CNS infections. More severe methotrexate neurotoxicity in our cohort is an important finding and needs further studies to understand the underlying cause.